2011
DOI: 10.1016/j.landurbplan.2010.12.018
|View full text |Cite
|
Sign up to set email alerts
|

Irrigation performance in private urban landscapes: A study case in Zaragoza (Spain)

Abstract: a b s t r a c tIrrigation water use in private landscapes represents an increasing share of total water use in semiarid areas. In this work, 102 households located in the Montecanal neighbourhood (Zaragoza, Spain) were analysed. Research took advantage of the dual water supply network (separate indoor and irrigation water networks). The analysis was based on bi-monthly water billing records for the period 2005-2007. The total household landscape area (93 m 2 ) and the area occupied by turf, trees and shrubs we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(44 citation statements)
references
References 22 publications
(45 reference statements)
1
36
0
4
Order By: Relevance
“…In WUCOLS, which is the first of the field-based methods, K L is determined by multiplying species, density and microclimate factors to determine the overall landscape coefficient [47][48][49].…”
Section: Field Datamentioning
confidence: 99%
“…In WUCOLS, which is the first of the field-based methods, K L is determined by multiplying species, density and microclimate factors to determine the overall landscape coefficient [47][48][49].…”
Section: Field Datamentioning
confidence: 99%
“…However, domestic gardens are usually over irrigated (Endter-Wada et al, 2008), although Salvador et al (2011) highlight that a water deficit occurs during the summer period as a result of Spanish holiday habits. Considering different irrigation schedule criteria would not alter the order of the designs according to energy consumption.…”
Section: Discussionmentioning
confidence: 99%
“…The values assumed for these factors were k s = 0.82, corresponding to turf (Salvador et al, 2011), k d = 1 (average density) and k mc = 0.9 (low, assuming that the garden is protected from the wind by nearby buildings and in most cases by perimeter fences, which will throw shadow onto the garden surface). The value for the landscape coefficient was 0.738, and the irrigation water doses were 495.4 and 1,174.7 L m -2 yr -1 for Girona and Elche, respectively.…”
Section: Irrigation Dosementioning
confidence: 99%
See 1 more Smart Citation
“…For example, Ferguson (1987) reported that 40 to 70% of residential water use in the United States was for landscapes but urban water use in the Ebro basin in Spain was only 7% which was mainly in cases of drought (Salvador et al 2011). …”
Section: Introductionmentioning
confidence: 99%